2021
DOI: 10.1155/2021/8876679
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure Characteristics and Permeability Prediction Model in a Cretaceous Carbonate Reservoir, North Persian Gulf Basin

Abstract: Due to the diversity of pore types, it is challenging to characterize the Middle East’s Cretaceous carbonate reservoir or accurately predict its petrophysical properties. In this paper, pore structure in the reservoir is first classified using a comprehensive method. Then, based on the identified pore structure types, a new permeability model with high prediction precision is established. The reservoir is dominated by 6 pore types, such as intergrain pores and moldic pores, and 6 rock types. Grainstone, algal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In combination with the characteristics of pore types, pore throat radius distribution and permeability, we qualitatively divided the PS of Kh2 into four types (Lu et al, 2021), the corresponding characteristic is shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In combination with the characteristics of pore types, pore throat radius distribution and permeability, we qualitatively divided the PS of Kh2 into four types (Lu et al, 2021), the corresponding characteristic is shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Kh2 is the major hydrocarbon‐producing member. Six rock types are developed in the Kh Formation, which is grainstone (RT1), algal packstone (RT2), algal wackestone (RT3), foraminiferal wackestone (RT4), mudstone (RT5) and echinoderm wackestone (RT6) (Lu et al, 2021). A large number of bioturbance structures result in strong heterogeneity of the reservoir in Kh2.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of shale reservoir pore types is the basis of shale reservoir evaluation. , The pore size of shale is small, and the pore morphology and genesis are diverse. The micro–nano connected pores and micro-fractures together form a pore network for gas occurrence and seepage. The mountain shales in the study area mainly develop intergranular pores and organic pores. The organic pores of the high-carbon siliceous shales are very well developed, with a predominantly rounded and subrounded morphology (Figure a,b), pore size usually greater than 100 nm, good connectivity, and an average porosity of 5.0% (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the effect of residual water saturation on the formation factor at standard and reservoir conditions. The formation factor generally indicates by how many times the resistivity of a partially water-saturated rock increases compared to its resistivity when the pore volume is fully saturated with water [28,29]. Moreover, since the volume of water in the pores of the rock samples does not change during the transition from the standard conditions to the reservoir conditions, the dependences of the formation factor on water saturation turn out to be close in this case.…”
Section: Figurementioning
confidence: 93%